FACTORS INFLUENCING LOW ANTENATAL CARE (K4) VISITS AMONG PREGNANT WOMEN AT SYAHRUDDIN CLINIC - Tanjung, Meni Fuzi Astuti; Br Barus, Sri Malemna (Cattleya Darmaya Fortuna, 2025)
Antenatal Care (ANC) is care provided during pregnancy until delivery. ANC is important to ensure that the natural process continues to run normally and to detect abnormalities in pregnant women so that complications that may occur during pregnancy can be detected early and adequately handled. If pregnant women do not undergo antenatal care checks, it will not be known whether their pregnancy is progressing well or experiencing high-risk conditions and obstetric complications that can endanger the life of the mother or fetus (Putri, 2012). This study uses a descriptive design. This method is used to solve or answer problems currently being faced in this situation or that is currently happening. Data analysis used is bivariate analysis, analysis to determine the relationship between the variables studied using the non-parametric chi-square test with a significance limit of 0.05. Data collection techniques used primary data and secondary data. Mothers' knowledge of antenatal care visits for 30 respondents was sufficient. The attitude of pregnant women towards the low number of antenatal care visits for 30 respondents was sufficient. Education of pregnant women towards antenatal care visits there are 30 respondents it can be concluded that the education of pregnant women towards antenatal care visits is sufficient, who have husband support towards antenatal care visits there are 30 respondents who get good husband support. The conclusion of the results of this study is from the square test of the most influential factors, it is known that the education factor has a large influence p value 0.047 <0.05, then the results of the square test are Ha accepted and Ho rejected, which means that there are factors that influence the low number of K4 antenatal care visits in pregnant women.